Contingency - Ami Clarke (Technophany)
The Leveson enquiry in the UK (2011–12) made something visible that many had suspected for a very long time: that politics was caught up in far too cosy relations between the politicians, the press, and the police, pouring doubt upon anything that might amount to a free press. The drift online, though, provided further layers to this, and I followed the move from paper to digital news reportage, and the subsequent changes to not only the ‘form’ of the news, the tempo and the style, but how these combine to inflect what it is even possible to say, to whom, and by whom, in the affectual realm of social media. There’s a long legacy of art and language over the past century, probing the burgeoning relationship between language and communication technologies, that question meaning making and reason, and the concept of free will, amidst fears of control.  In this century, questions of access, privilege, and the rights to knowledge are exemplified by online flame wars amidst the distracting cries of ‘fake’ news, with access to knowledge a key driver for social and economic development as Wikimedia, Hannah Arendt, and Mercedes Bunz can all attest. Shoshana Zuboff’s fieldwork shows how the new knowledge territories emerging alongside the capacity to analyse processes and behaviours, also result in political conflict over the distribution of knowledge, as surveillance capitalists “declared their right to know, to decide who knows, and to decide who decides.”